Сучасні технології: виклики та ризики - Владленова, Іліана Вікторівна (НТУ "ХПІ", 2014)
У статті аналізуються ризики, до яких приводять технології, розглядається феномен технізації людської природи, що провокує трансформовану самосвідомість, трансформацію етичних цінностей. Можливо також використання біологічних компонентів для оптимізації технічних процесів (виділення з біологічного середовища і переведення в технічну систему). У такому разі кардинально зміняться уявлення про природу тілесності. Проблема трансформації соціальної природи людини актуалізується у зв’язку з необмеженими можливостями маніпуляції при широкому використанні високих технологій в суспільстві.

A number of driving forces have been identified that are shaping our modern world and have a strong influence on the risks we face. The article analyzes the risks to which leading technology, mechanization. The benefits of modern technology often involve health, safety and environmental risks that produce public suspicion of technologies and aversion to certain products and substances. The phenomenon of human nature that provokes a transformed consciousness, transformation ethical values. You may also use biological components for optimization of technical processes (separation of the biological environment and transfer to the technical system). If so radically changed ideas about the nature of physicality. The problem of transforming social nature of man is updated due to the unlimited possibilities of manipulation with extensive use of high technology in society.
Modern technologies: challenges and risks
Keywords: високі технології; ідентичність; природа людини; етичні цінності; high technology; identity; human nature; moral values